A NEW TECHNIQUE FOR SWEAT CHLORIDE DETERMINATION USING MOHR’S SILVER METHOD: DEVELOPEMENT AND ANALYTICAL VALIDATION - Laoufi, Nardjess Rim; Bouchenak, Farida; Zouakh, Amina; Abdelaziz, Mouna; Zerrouk, Abdelhakim; Saddouki, Djamal (university of el oued/جامعة الوادي, 2023)
This study presents a new technique for determining chloride ions in the sweat test for the diagnosis of cystic fibrosis. The technique developed is based on Mohr’s silver titrimetric method. The analytical development was performed on three quality control levels (C1, C2 and C3 at 25, 45 and 65 mmol/L respectively) and validated according to the requirements of ISO15189. Repeatability was estimated by the coefficient of variation (CV) at 2.45%, 3.12% and 2.21% for C1, C2 and C3. The CV estimated the intermediate precision at 4.12%, 4.51% and 2.63% for C1, C2, C3. The bias estimated the accuracy at 0.99% for C1, 2.76% for C2 and 2.55% for C3. The assays were performed following a linear calibration curve (equation: Y=0.0001 X + (3 x 10-5) with R2 =0.9995) between 0 and 150 mmol/L. This new technique is a simple and fast alternative using stable and less toxic reagents than the mercurimetric technique
Article
Keywords: cystic fibrosis; sweat test; Mohr’s method; analytical validation; sweat chlorides.